Gambaran Histopatologi Rumen dan Retikulum Sapi Bali Akibat Adanya Benda Asing - Eldarya Envisari Depari; Annas Farhani; I Wayan Batan; I Made Kardena (Jurnal Sain Veteriner, 2017)
Rumen and reticulum hold an important role in the ruminant’s digestive tract. During the meal, Bali cattle accidentally ingest foreign objects because they can’t distinguish between foreign body object and feed. Cattles do not really chew food before swallowing. This study aims to determine the existence of a foreign body in the stomach and histopathological overview of Bali cattle rumen and reticulum due to a variety of foreign objects. This study used 10 samples of cattle Bali consisting of nine samples of rumen and reticulum contained foreign objects (plastic, metal, wood and stone) and one normal sample of the rumen and reticulum Bali cattle. Samples were obtained from Slaughter House at Mambal, Abian Semal District, Badung regency, Bali. Based on the results of research conducted on the rumen and reticulum Bali cattle, there are a variety of foreign objects such as plastic, metal, wood and stone. Histopathological changes in the mucosa of the rumen and reticulum form of inflammatory cell infiltration from mild to severe. Conclusions from this research that found a foreign body object in the rumen and reticulum Bali cattle, and foreign body objects cause tissue destruction.